Dysbiosis in the oral bacterial and fungal microbiome of HIV-infected subjects is associated with clinical and immunologic variables of HIV infection - Mukherjee, Pranab K.; Chandra, Jyotsna; Retuerto, Mauricio; Tatsuoka, Curtis; Ghannoum, Mahmoud A.; McComsey, Grace A. (PloS one, 2018)
The effect of smoking on microbial dysbiosis and the potential consequence of such shift on markers of HIV disease is unknown. Here we assessed the relationship of microbial dysbiosis with smoking and markers of HIV disease. Oral wash was collected from: (1) HIV-infected smokers (HIV-SM, n = 48), (2) HIV-infected non-smokers (HIV-NS, n = 24), or (3) HIV-uninfected smokers (UI-SM, n = 24). Microbial DNA was extracted and their bacterial and fungal microbiota (bacteriome and mycobiome, respectively) were characterized using Ion-Torrent sequencing platform. Sequencing data were compared using clustering, diversity, abundance and inter-kingdom correlations analyses. Bacteriome was more widely dispersed than mycobiome, there was no noticeable difference in clustering between groups. Richness of oral bacteriome in HIV-SM was significantly lower than that of UI-SM (P ≤ .03). Diversity of HIV-NS was significantly lower than that of HIV-SM or UI-SM at phylum level (P ≤ .02). Abundance of Phylum Firmicutes was significantly decreased in HIV-NS compared to HIV-SM and UI-SM (P = .007 and .027, respectively), while abundance of Proteobacteria was significantly increased in HIV-NS compared to HIV-SM and UI-SM (P = .0005 and .011, respectively). Fungal phyla did not differ significantly between the three cohorts. Cumulative smoking was positively correlated with Facklamia but negatively with Enhydrobacter, and current alcohol use was negatively correlated with Geniculata. Bacteria Facklamia exhibited weakly positive correlation with longer PI duration (r = 0.094, P = 0.012), and a negative correlation with nadir CD4 count (r = -0.345; P = 0.004), while Granulicatella was negatively correlated with nadir CD4 count (r = -0.329; P = 0.007). Fungus Stemphylium correlated negatively with nadir CD4 (r = -0.323; P = 0.008). Dysbiosis of the oral microbiota is associated with clinical and immunologic variables in HIV-infected patients.